In the Closed Room - Burnett, Frances Hodgson, 1849-1924 (Salt Lake City, UT : Project Gutenberg, 2004)
"In the Closed Room" by Frances Hodgson Burnett is a novel written during the late 19th century, showcasing the author$1 (Bs signature blend of fantasy and reality. This book delves into themes of childhood innocence, the search for identity, and the interconnection between life and the afterlife. The story primarily unfolds through the experiences of a young girl named Judith, who feels a profound sense of displacement from her mundane surroundings. The narrative follows Judith, a frail and curious child living in a cramped apartment with her hardworking parents. As she grapples with her solitude and the chaotic noise of city life, she discovers a magical "Closed Room" in a nearby abandoned house, where she meets the ghostly presence of a little girl resembling Aunt Hester, her deceased ancestor. Their interactions reveal a world of imagination and a longing for connection that transcends the limitations of Judith's reality. The book beautifully portrays Judith's internal struggle and her journey toward discovering her true self and the wonders that lie beyond her everyday life, culminating in a touching exploration of love, loss, and the bittersweet nature of childhood memories. (This is an automatically generated summary.)s
Release date is 2004-07-01
Produced by Paul Hollander, Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Girls -- Juvenile fiction; Ghosts -- Juvenile fiction